Oncolytic measles virotherapy and opposition to measles vaccination - Russell, Stephen J.; Babovic-Vuksanovic, Dusica; Bexon, Alice; Cattaneo, Roberto; Dingli, David; Dispenzieri, Angela; Deyle, David R.; Federspiel, Mark J.; Fielding, Adele; Galanis, Evanthia; Lacy, Martha Q.; Leibovich, Bradley C.; et al. (Mayo Clinic proceedings, 2019)
Recent measles epidemics in US and European cities where vaccination coverage has declined are providing a harsh reminder for the need to maintain protective levels of immunity across the entire population. Vaccine uptake rates have been declining in large part because of public misinformation regarding a possible association between measles vaccination and autism for which there is no scientific basis. The purpose of this article is to address a new misinformed antivaccination argument—that measles immunity is undesirable because measles virus is protective against cancer. Having worked for many years to develop engineered measles viruses as anticancer therapies, we have concluded (1) that measles is not protective against cancer and (2) that its potential utility as a cancer therapy will be enhanced, not diminished, by prior vaccination.
Gesehen am 07.04.2020